Neurological Sequalae in Survivors of Perinatal Asphyxia - Tjipta Bahtera; Santoso Suroso; Bambang Darmanto (Paediatrica Indonesiana, 1992)
Perinatal asphyxia is the most common cause of either death or severely handicapped survivors. Perinatal asphyxia can be identified by one, five, ten minutes APGAR scores less than 7. Prolonged asphyxia produce hypoxemia, acidosis, hypercapnia, thus diminishing cerebral blood flow, which in turn results in clinical patterns of Hypoxic - Ischemic Encephalopathy (HIE). The atm of this study was to evaluate the accuracy of clinical observation on newborn asphyxia to predict the presence of neurological deficits connected with blood gas analysts investigation. Thirty eight newborn babies who bad APGAR scores of less than 7 as an asphyctic newborn baby group compared with an equal number of normal babies as control group. Physical and neurological examinations were performed immediately after birth and at six months of age. Two of the 38 infants who bad perinatal asphyxia died several hours after birth. Two of the 31 of the surviving infants with a historical of perinatal asphyxia bad cerebral palsy. One of the two babies with cerebral palsy bad epilepsy. Twenty nine of the 31 of the surviving infants with a history of perinatal asphyxia with or without mild HIE showed normal neurological outcomes. All of the normal newborn babies as control showed normal neurological outcome. One infant with cerebral palsy and one infant who bad cerebral palsy with epilepsy bad a history of a severe degree of HIE and moderate degree of Hm with neonatal convulsion respectively. One of the 2 infants with cerebral palsy bad severe hypoxia and none on the infants with normal neurological outcome exhibited Pa02 less than 50 mmHg. There were no significant differences ( p > 0.05) of the Pa02 PH and base deficit between the infants with a history of asphyxia and with a history of a vigorous baby, who bad a normal outcome. We concluded that postasphyxia encephalopathy was more accurate than a low APGAR score in predicting an adverse outcome, and the value of the Pa02 very important in predicting an encephalopathy.